Seismic response of critical interdependent networks. - Dueñas-Osorio, Leonardo
During the last decade, critical infrastructure systems such as electric power, water distribution, transportation and telecommunications have been stressed by significant natural hazards and human errors leading to malfunction. Earthquakes, blackouts and satellite failures have evidenced the vulnerability of these growing networked systems threatening the continuity of the United States' economy. The potential for malicious perturbations to these systems is also an important current concern. However, the underlying susceptibility of these networks to disruptive events is in large part due to the increasingly complex pattern of interdependencies that tie these civil infrastructures together. This paper mainly investigates the effect of seismic disruptions on the performance of real interdependent networks. Maintenance-induced malfunctions and coordinated attacks are also studied for completeness. Several degrees of interconnectedness are explored. Interdependent network fragility curves are introduced to display the effect of these different strengths of coupling. Characterization of the performance displayed by the networks is utilized to propose mitigation actions and study propagation of their effects. It is shown that minimal strategic interventions propagated through the network can generate a more resilient interdependent entity.
Keywords: Interdependent networks; Seismic fragility; Infrastructure systems; Cascading failures; Network functionality; Seismic mitigation